Exploring endophytic fungi from Rhizophora spp leaves for improving plant growth. Issue 1 (1st June 2022) - Elfiati, D; Delvian; Syafitri, M; Hidayat, A
Abstract: Endophytic fungi are a group of fungi inhabiting the plant tissue for part or all of their life cycle without exposing any hazard to the host. Endophytic fungi can produce bioactive chemicals or secondary metabolites in proportion to their host plant, therefore no parts of the plant are needed to obtain these compounds. As a result, the survivability of a plant survival is maintained. The aim of this study was to obtain endophytic fungi isolated from the leaves of Rhizophora mucronata and Rhizophora apiculata. R. mucronata and R. apiculata leaves were collected at random in Lubuk Kertang Village, West Brandan District, Langkat Regency, North Sumatra. Endophytic fungal isolation was conducted on potato dextrose agar (PDA) medium. The fungal isolates were morphologically identified to the genera level. In this study, 8 isolates from R. mucronata leaves and 9 isolates from R. apiculata leaves were obtained. According to morphological identifications, a total of 8 endophytic fungal isolates from R. mucronata leaves belonged to the genus Aspergillus, while 9 isolates from R. apiculata leaves belonged to three genera: Aspergillus (7 isolates), Cunninghamella (1 isolate), and Humicola (1 isolate).